The role of tolvaptan add-on therapy in patients with acute heart failure: a systematic review and network meta-analysis - Pratama, Vireza; Budiono, Jordan; Thobari, Jarir At; Widyantoro, Bambang; Anggraeni, Vita Yanti; Dinarti, Lucia Kris (Frontiers in Cardiovascular Medicine, 2024)
Background: Several conflicting reviews have concluded that the use of loop diuretics is associated with poorer clinical and safety outcomes. Therefore, this research aimed to investigate the efficacy and safety of tolvaptan as an adjunct to conventional diuretics in patients experiencing acute heart failure (AHF). Methods: A comprehensive search was conducted on databases, comprising PubMed, EMBASE, ProQuest, EBSCO, and Cochrane Library up to May 2023 to identify randomized controlled trials comparing the effects of tolvaptan with conventional therapy and placebo in AHF patients. The quality of the included trials was evaluated using the Cochrane risk of bias. Network meta-analysis (NMA) was conducted to examine the dosage effect of tolvaptan.Result: A total of 17 studies with 18 reports, consisting of 10,039 patients, were selected. The addition of tolvaptan significantly alleviated dyspnea [24h: RR 1.16 (1.04, 1.29), 48h: RR 1.18 (1.04, 1.33)], reduced body weight up to 48h [Asia group: MD -0.93 (-1.48, -0.38), Non-Asia group: MD -2.76 (-2.88, -2.65)], diminished edema [RR 1.08 (1.02, 1.15)], increased serum sodium 3.78)], and resulted in a change in serum creatinine [MD -0.10 (-0.18, -0.01)]. No significant differences were observed in mortality and rehospitalization. NMA suggested that an intermediate dosage (15 mg/day) might have achieved the best efficacy in reducing dyspnea at 24h, decreasing edema, increasing serum sodium, and lowering the incidence of worsening renal function (WRF).In conclusion, a meta-analysis showed that tolvaptan contributed to the short-term alleviation of congestion symptoms, elevated sodium levels, and a lower incidence of WRF. However, no significant benefits were observed in long-term symptoms, rehospitalization rates, and mortality. An intermediate dosage of tolvaptan might be considered the optimal choice for various clinical outcomes.